INVESTIGATING COGNITIVE AND METACOGNITIVE STRATEGY USE DURING AN ENGLISH PROFICIENCY TEST - Wenxia Zhang; Meihua Liu (Universitas Katolik Indonesia Atma Jaya, 2008)
This paper reports on the results of a study of cognitive and metacognitive strategy use and its effect on the students’ test performance at the tertiary level in a Chinese EFL context. A 18-item survey involving 526 undergraduate non-English majors revealed that: (1) the students had a medium use of both cognitive and metacognitive strategies during the test; (2) cognitive and metacognitive strategy use was closely related to each other, but neither was a predictor for the other; and (3) though cognitive and metacognitive strategy use significantly correlated with the students’ performance in certain parts of the proficiency test, only the metacognitive strategy of evaluating one’s performance proved to be a positive predictor of the students’ performance in listening and reading comprehension and the overall written test. Based on the results, some implications and suggestions for future research are discussed. Keywords: Strategy use; Cognitive; Metacognitive; Test performance; Tertiary